Luck egalitarianism as providence - Rosen, Shlomo Dov (International journal of philosophy and theology, 2017)
Luck egalitarianism is an approach within current distributive justice theory which aims to focus redistributive efforts solely upon disadvantages that ensue from bad luck. This article considers how central assumptions and themes of both luck egalitarianism and its critics parallel those of providence theology and share some of their concerns. These relate to problems such as the basis of equality, the extent and nature of our knowledge, and of course, the paternalism that assessing people’s responsibility over their own disadvantages involves. I highlight the similarity of luck egalitarianism to the role of providence and providence theory thinking, and particularly the tension between egalitarianism as a theological concept and the condescension inherent to imitatio Dei ethics. I approach these issues by analyzing standard criticisms of the luck egalitarian project, espoused by Susan Hurley and Elizabeth Anderson. I then proceed to assess the values of luck egalitarianism itself and consider different models of providence, and the meaning of this analysis for normative ethics. The subject matter of this article is part of a wider comparison of distributive justice and providence theory, within which luck egalitarianism affords a very fruitful and highly relevant case study.